Effects of palm oil supplementation in broiler diets - Panja, Paichok; Hamid, Kassim; Syed Salim, Syed Jalaludin (Asian-Australasian Association of Animal Production Societies, 1995)
A study was conducted to determine the effects of varying palm oil levels (0 to 8%) in the diets on the performance of broilers under the warm humid tropical environment. Increasing palm oil levels resulted in corresponding rise in the dietary energy concentrations, and broilers fed on higher energy diets improved feed and energy consumption, daily weight gain and feed conversion ratio. Total carcass fat content was found to increase at higher levels of palm oil inclusions.